Urban Planning Seen Through the Process of Establishing Substitute Land in the Edo Period. Issue 2 (1st May 2018) - Lee, Kilhun
Abstract : What was the process of decision-making when hiyokechi were established and substitute land provided in Edo? This study aims to clarify the shogun′s logic in considering the urban planning of Edo, which occurred through the confiscation of land and transfer of substitute land. This paper has two foci: the actual conditions and distribution of the substitute lands, and the process of how these lands were allocated. The results of the study arrive at two conclusions: 1) Substitute land was based on the bashogara, which was the grade of land in the town; 2) Edo expanded through this process of redistributing land through substitute land.